Recycled polypropylene coffee husk and coir coconut biocomposites: morphological, mechanical, thermal and environmental studies (2019)
In this work, biocomposites based on recycled polypropylene (r-PP) and two different natural fibers (coffee husk-CHF and coconut coir-CCF fibers) were prepared using extrusion and injection molding processes. Also, the addition of maleated polypropylene (MAPP) as a coupling agent on the biocomposites was explored. Recycled polypropylene and its biocomposites were tested following ASTM standards in order to evaluate tensile and flexural mechanical properties. Also, thermal behavior and the morphology of these materials have been studied by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and scanning electronic microscopy (SEM). The experimental results showed that the addition of CHF and CCF to the r-PP resulted in an increase in the flexural modulus and thermal properties of the composites but resulted in poor impact properties. Thermal characterization showed that CHF possesses a better thermal stability compared to CCF. However, both fibers act as nucleating agents and generate an increase in the thermal stability of the r-PP phase. Finally, it was observed that addition of 4% of MAPP significantly improved the mechanical strength and impact behavior of the biocomposites. Regarding environmental issues, a cradle to gate life cycle assessment was made in order to define the carbon footprint of the materials.